Novel 8-Hydroxyquinoline Derivatives as Multitarget Compounds for the Treatment of Alzheimer's Disease - Prati, Federica; Bergamini, Christian; Fato, Romana; Soukup, Ondrej; Korabecny, Jan; Andrisano, Vincenza; Bartolini, Manuela; Bolognesi, Maria Laura (ChemMedChem, 2016)
We discovered a small series of hit compounds that show multitargeting activities against key targets in Alzheimer's disease (AD). The compounds were designed by combining the structural features of the anti-AD drug donepezil with clioquinol, which is able to chelate redox-active metals, thus decreasing metal-driven oxidative phenomena and β-amyloid (Aβ)-mediated neurotoxicity. The majority of the new hybrid compounds selectively target human butyrylcholinesterase at micromolar concentrations and effectively inhibit Aβ self-aggregation. In addition, compounds 5-chloro-7-((4-(2-methoxybenzyl)piperazin-1-yl)methyl)-8-hydroxyquinoline (1 b), 7-((4-(2-methoxybenzyl)piperazin-1-yl)methyl)-8-hydroxyquinoline (2 b), and 7-(((1-benzylpiperidin-4-yl)amino)methyl)-5-chloro-8-hydroxyquinoline (3 a) are able to chelate copper(II) and zinc(II) and exert antioxidant activity in vitro. Importantly, in the case of 2 b, the multitarget profile is accompanied by high predicted blood-brain barrier permeability, low cytotoxicity in T67 cells, and acceptable toxicity in HUVEC primary cells.
Keywords: Donepezil; Cell Survival; cholinesterases; oxychinolin; Alzheimer′s disease; Humans; β-amyloid; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; indany; Copper; hematoencefalická bariéra; Blood-Brain Barrier; Indans; Zinc; lidé; Alzheimer Disease; Antioxidants; Alzheimerova nemoc; amyloidní beta-protein; zinek; Human Umbilical Vein Endothelial Cells; chelation; Piperidines; cholinesterasové inhibitory; Drug Design; měď; antioxidancia; donepezil; butyrylcholinesterasa; Amyloid beta-Peptides; Clioquinol; antioxidants; endoteliální buňky pupečníkové žíly (lidské); racionální návrh léčiv; nádorové buněčné linie; chelátory; inhibitors; jodchlorhydroxychin; piperidiny; Cell Line, Tumor; Oxyquinoline; Cholinesterase Inhibitors; Butyrylcholinesterase; Chelating Agents; viabilita buněk